Concept mapping teaching method and nursing education: a systematic review and meta-analysis - Faraji, Azam; banafshi, Zhina; Jalali, Rostam; Jalali, Amir (BMC medical education, 2025)
Concept map is a novel metacognitive approach in education that can improve critical thinking and decision making skills in students and nurses. Therefore, the current systematic review and meta-analysis was conducted aimed to determine the effect of the concept map approach in nursing education. The present systematic review and meta-analysis was performed to analyze the published studies in the no time limit until Sep. 2024 according to the PRISMA 2020 guideline. Articles related to the purpose of the study were obtained from MagIran, SID, ProQuest, PubMed, Scopus, and Web of science (WoS) databases, and Google Scholar search engine using relevant and validated keywords. Heterogeneity among studies was examined using the I index and Egger's regression intercept was used to examine the publication bias. In the initial search, 579 studies were found, of which finally 44 articles with a sample size of 1722 people in the intervention group, and 1712 people in the control group were included in the meta-analysis. As a result of combining the studies, the educational performance score in the intervention group increased more than the control group [95% confidence interval: (1.693 ± 0.194, P < 0.001)]. The results of the subgroup analysis showed that the positive effect of performing concept map is more in the nursing students than working nurses, although this result was not statistically significant (P ˃ 0.05). The results of this study showed that the concept map has significantly increased the performance of nursing education. The results of this study can be considered by educational and therapeutic policy makers.